Resistivity Tunnel Monitoring System - Firman Syaifuddin; Amien Widodo; Muhammad Nurul Puji (Institut Teknologi Sepuluh Nopember, 2018)
The development of an urban area must be supported by the construction of infrastructure such as public facilities. The crowded of urban area in Indonesia increasingly requires the existence of a mass transportation mode that is capable of carrying passengers in large amounts and relatively quickly. Recently Jakarta has proposed the construction of the MRT (Mass Rapid Transit) with underground lines utilize tunnel technology. Tunnel system was chosen as an alternative solution socioeconomic problems in the land problem and conditions of the existing urban planning. The geographical position of Indonesia is located in the equatorial zone which is the weather conditions have high levels of weathering and moisture or high humidity, this condition may result in changes in the level of strength of rock of the tunnel system in a relatively fast. In the construction of public facilities with the tunnel system need monitoring system the condition of the tunnel to avoid the dangers that may occur due to the failure of a tunnel system. To determine the level of moisture and water content in the rock or overburden a tunnel can be determined by utilizing the resistivity method. Resistivity method is a geophysical method that measures the magnitude of the resistivity of a material. Changes in moisture content and humidity levels of rock or soil in an area can be indicated by a change in the value of resistivity of rock or soil. In the measuring of the resistivity method needed good design to provide accurate information, especially if it will be used as a monitoring system for a tunnel. Development of measuring the resistivity method, and in particular data processing is done with the aim of optimizing the measurement process and the measurement results can be interpreted easily and be able to demonstrate a phenomenon that occurs in rocks or soil cover tunnel.